Information behaviour characteristics of project actors in organisation management - Frank Dzokoto; Francis Edum-Fotwe; Peter Demian (2013)
Research shows that a large proportion of the working time of project actors is spent processing, communicating and disseminating information that is not relevant to their tasks. This makes information overload (IO) a liability that adversely affects the performance of project actors and the management of their organisations. Some advances have been achieved in structuring information resources to support the decision making process of engineering project actors. However, it is not always possible to structure and direct the right information to the right actor at the right time. Some engineering companies have taken the initiative of resolving this problem by encouraging actors to employ personal information management systems, information sifting systems, product data management systems and other software applications to help manage the problem of IO. These information systems rely on pull technology which contribute towards time delay, inefficiency and cost in actors’ information seeking process. The paper draws on information behaviour (IB) literature of engineering project actors to establish a platform for future studies on how IB can inform how information could be structured and made available to the right actor at the right time to facilitate timely decision making and organisation management. This paper proposes the SMART Push information capturing and delivery framework as a solution to IO. This could aid releasing the actor from the entire problem associated with information seeking process in order to focus on the task at hand.